Kinetika Reaksi Reduksi Ion Logam Tembaga pada Limbah Industri Elektroplating dengan Proses Elektrokoagulasi - Emi Erawati; Kesi Marfiana (Eksergi, 2020)
The electroplating process not only produces useful products but also produces waste. Copper is one of the elements contained in waste. Waste containing copper has a major impact on the environment and human health if there is no prior treatment. One way to reduce copper levels in electroplating waste is the electrocoagulation process. This study aims to investigate the efficiency of reducing the concentration of waste at various concentrations and types of electrodes and to determine the reaction rate constants of the first and second order reactions. 60, 80 and 100 mL electroplating waste were diluted with distilled water in a 500 mL measuring flask. The two plates were clamped using a statif and a 3/4 plate immersed in wastewater. The cathode and anode are connected to a 12 volt power supply with a distance between the electrodes of 2 cm and a stirring speed of 200 rpm. Samples were taken every 0; 40; 80; 120; and 160 minutes to test Cu content with AAS. Repeating the same steps for various types of electrodes, namely Al, Fe, and CuZn. The highest efficiency at various concentrations of 80 mg/L and types of electrodes of Fe were 67.66% and 92.82% in that order. The rate constants of the first and second order reactions are 0.0096 s-1 and 0.0058 ppm1 .s-1 respectively